From Wng to Καιέχως: a possible explanation for the cartouche name KꜢ-kꜢ.w? - Theis, Christoffer (Journal of Egyptian history, 2021)
Abstract So far, it has not been possible to equate the name KꜢ-kꜢ.w of the second king Horus Rꜥ-nb(=i) of the Second Dynasty, written in a cartouche during the Ramesside Period, with a name attested at the time of this dynasty. Taking into account the theory advanced by Jochem Kahl that Horus Rꜥ-nb(=i) is the same ruler as Wng, it is possible to develop a sequence in Hieratic script which leads from Wng to KꜢ-kꜢ.w and is based on a misreading of an Egyptian scribe.
Gesehen am 07.02.2022